2015
DOI: 10.1073/pnas.1408766112
|View full text |Cite
|
Sign up to set email alerts
|

Charge-mediated influence of the antibody variable domain on FcRn-dependent pharmacokinetics

Abstract: SignificanceTherapeutic antibodies of the immunoglobulin G (IgG) isotype show a pharmacokinetic (PK) profile that is strongly mediated by the interaction with the neonatal Fc receptor (FcRn). Therefore, modulating the FcRn–IgG interaction allows altering PK characteristics of therapeutic antibodies. So far, engineering the crystallizable fragment (Fc) is known to affect PK, and, although the influence of the antigen binding fragment (Fab) on FcRn interactions has been reported, the underlying mechanism remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
213
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(245 citation statements)
references
References 46 publications
(62 reference statements)
17
213
0
Order By: Relevance
“…Some, but not all, of these differences can be ascribed to physiochemical characteristics of the variable sequences. 46 In addition, the hinge domain that links the Fab to Fc domain also plays a role in the mFcRn-IgG affinity. 47 Interestingly, the protein A/G binding site on the Fc domain overlaps with the FcRn binding site, yet neither the variable or hinge domain of an IgG molecule influence the binding of an IgG to protein A/G protein.…”
Section: Resultsmentioning
confidence: 99%
“…Some, but not all, of these differences can be ascribed to physiochemical characteristics of the variable sequences. 46 In addition, the hinge domain that links the Fab to Fc domain also plays a role in the mFcRn-IgG affinity. 47 Interestingly, the protein A/G binding site on the Fc domain overlaps with the FcRn binding site, yet neither the variable or hinge domain of an IgG molecule influence the binding of an IgG to protein A/G protein.…”
Section: Resultsmentioning
confidence: 99%
“…S1). A previous report suggested that this increase in apparent affinity may be due to charge driven interactions between the variable region of briakinumab and FcRn, 17 so we additionally assessed the affinity of F(ab')2 constructs. In concordance with the previous finding, briakinumab displayed binding to FcRn regardless of the buffer pH, while neither of the other antibodies displayed any appreciable binding ( Fig.…”
Section: Fcrn Affinity Measurement Via Biolayer Interferometrymentioning
confidence: 99%
“…[9][10][11][12][13][14] In addition to Fc engineering efforts, multiple studies have reported disparate PK parameters in antibodies with identical Fc regions but different variable regions. [15][16][17][18][19][20] In particular, clearance rates are increased in antibodies with polyreactive [21][22][23] or cross-reactive 24,25 profiles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1–4 Recent studies have also shown that changes in the charge distribution on the protein surface could alter mAb pharmacokinetics (PK) by affecting FcRn-IgG dissociation. 5,6 Thus, the potential risk of deamidation at each site needs to be evaluated to ensure product stability.…”
Section: Introductionmentioning
confidence: 99%